Nutrition and Inflammation Influence 1-Year Mortality of Surgically Treated Elderly Intertrochanteric Fractures: A Prospective International Multicenter Case Series. (21st January 2019) - Belangero, William; Barla, Jorge Daniel; Rienzi Bergalli, Daniel Horacio; Olarte Salazar, Carlos Mario; Fernandez, Daniel Schweitzer; Mite Vivar, Miguel Angel; Zylberberg, Alejandro; Carabelli, Guido Sebastian; Kfuri, Maurício
Introduction: Hip fracture is a common and devastating event in older adults causing increased dependence, comorbidity, and mortality. Since new surgical techniques have not significantly improved the mortality rate, a better understanding of patient risk factors could improve the treatment algorithm and outcomes. This prospective study aimed to document the 1-year survival rate of patients with intertrochanteric fracture treated surgically in Latin America and to investigate risk factors associated with 1-year mortality. Patients and Methods: Between January 2013 and March 2015, 199 patients were prospectively enrolled. Inclusion criteria were aged 60 years or older, isolated intertrochanteric fracture (AO/OTA 31-A), and time to surgery within 10 days after injury. The follow-up period was 1 year. The association between mortality and patient demographics, comorbidity, surgical details, and preoperative laboratory parameters was assessed using log-rank tests. Results: Twenty patients died by 365 days after surgery (including 5 that died within 30 days of surgery) resulting in a 1-year survival rate of 89.8% (95% confidence interval = 84.6-93.3). The 1-year mortality was significantly associated with age (≥85 years old, P = .032), existing comorbidity ( P = .002), preinjury mobility level ( P = .026), mental state (Mini-Mental State Examination > 23, P = .040), low preoperative plasma albumin level ( P = .007), and high preoperative blood C-reactive protein level (CRP; P = .012). At the 1-year follow-up, patients on average did not regain their preinjury hip function and mobility, although the self-assessed quality of life was equal or better than before the injury. Discussion: As a prospective study, the current patient population had clear inclusion and exclusion criteria and was relatively homogeneous. The resulting associations between 1-year postoperative mortality and preoperative hypoalbuminemia and preoperative elevated CRP level are therefore especially notable. Previously identified risk factors such as male gender and time to surgery showed no significant association with 1-year mortality—the overall favorable condition of the current population or the lack of statistical power maybe responsible for this observation. Conclusion: The current results showed that under the condition of optimal surgical treatment and low surgery-related complication, preinjury health status as indicated by the blood level of albumin and CRP has a direct and significant impact on 1-year mortality rate.